Gadamer : a philosophical portrait - Di Cesare, Donatella; Keane, Niall (Bloomington : Indiana University Press, 2013)
Hans-Georg Gadamer (1900-2002), one of the towering figures of contemporary Continental philosophy, is best known for Truth and Method, where he elaborated the concept of "philosophical hermeneutics," a programmatic way to get to what we do when we engage in interpretation. In this book, the author highlights the central place of Greek philosophy, particularly Plato, in Gadamer's work, brings out differences between his thought and that of Heidegger, and connects him with discussions and debates in pragmatism. This is a sensitive philosophical portrait of one of the twentieth century's most powerful thinkers.
Living through a century -- The event of truth -- Lingering in art -- On the way to philosophical hermeneutics -- The constellation of understanding -- An ethics close to life -- The enigma of Socrates : philosophical hermeneutics and Greek philosophy -- The horizon of dialogue -- Hermeneutics as philosophy -- Keeping the dialogue going.
Originally published in Italian, 2007.
Includes bibliographical references and indexes.
English.
JSTOR
Keywords: Gadamer, Hans-Georg, -- 1900-2002.; Gadamer, Hans-Georg, -- 1900-2002; Philosophers -- Germany; Philosophes -- Allemagne; PHILOSOPHY -- History & Surveys -- Modern; PHILOSOPHY -- Movements -- Phenomenology; Philosophers; Germany